ROLE OF TEACHERS STRATEGIES IN FOSTERING STUDENTS METACOGNITION - Melinda, Dian Anggriani; Wulan, Ana Ratna (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
The importance of critical thinking has triggered many educators to develop this ability on their students. This research aim was to explore the role of teachersâ strategies in fostering studentsâ metacognitive strategies on their critical thinking abilities. 135 students and 5 teachers from 5 different high school in Sumedang district were involved in this research. Teachersâ strategies were explored through observation whereas studentsâ critical thinking abilities were explored through questionnaire. Observations showed that each teacher fostered studentsâ metacognitive strategies differently. Kruskal-Wallis Test showed there is significant difference between studentsâ critical thinking abilities based on their teachersâ strategies. It implies the effect of teachersâ strategies to studentsâ critical thinking abilities. The more teachers foster their studentsâ metacognitive strategies, the higher their studentsâ critical thinking abilities. By means, there is possibility to develop studentsâ critical thinking ability through their metacognitive strategy.